Prognostic and clinical pathological significance of the systemic immune-inflammation index in urothelial carcinoma: a systematic review and meta-analysis - Wang, Yao; Hao, Xiaoming; Li, Gang (Frontiers in Oncology, 2024)
Background A new non-invasive biomarker, the Systemic Immune-Inflammation Index (SII), has been proven to have prognostic value in multiple cancers. This systematic review and meta-analysis aimed to investigate the prognostic and clinical pathological significance of SII in urothelial carcinoma. Methods A comprehensive search was conducted across multiple databases, including PubMed, Web of Science, Embase, Cochrane Library, and CNKI. The quality of the included studies was assessed using the Newcastle-Ottawa Scale (NOS). Hazard ratios (HR) with 95% confidence intervals (CI) were calculated to evaluate the prognostic value of SII before treatment on survival outcomes, and odds ratios (OR) with 95%CI were used to assess the correlation between SII before treatment and clinical pathological features. Results This meta-analysis included a total of 10 studies (11 datasets) with 6,333 patients. The pooled analysis showed that high SII before surgery was significantly associated with poor survival outcomes in patients with urothelial carcinoma, including overall survival (OS) (HR=1.55, 95%CI 1.24-1.95, p<0.001), cancer-specific survival (CSS) (HR=2.74, 95%CI 1.67-4.49, p<0.001), recurrence-free survival (RFS) (HR=2.74, 95%CI 1.67-4.49, p<0.001), and progression-free survival (PFS) (HR=1.66, 95%CI 1.36-2.02, p<0.001). In addition, patients with elevated preoperative SII values were more likely to have adverse pathological features, including larger tumor size and advanced pathological T stage (p<0.001). Conclusion These findings suggest a significant association between high SII levels before treatment and poor survival outcomes, as well as certain clinical pathological features, in patients with urothelial carcinoma.